Representasi Budaya Lokal dalam Novel Manusia Belang Karya Alfian Dippahatang: Kajian Semiotika Budaya Umberto Eco - Asmawati, Asmawati; Nensilianti, Nensilianti; Faisal, Faisal (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract. This study aims to describe the symbolic meaning and form of cultural representation of the To Balo tribe contained in the novel Human Belang which is used as a source of data being analyzed. This study uses a descriptive qualitative method by describing the data obtained based on Umberto Eco's Semiotics theory. The data source for this research is the novel Human Belang by Alfian Dippahatang published in 2020 by BasaBasi publishing house with thickness viii + 160 pages. The results of this study show two descriptions in the analysis of symbolic meaning, namely the symbol of sincerity showing surrender or willingness to the situation that is being passed due to the loss of someone in the novel. The symbol of trust shows belief in something that is believed to exist or be true. Meanwhile, the to balo culture represented in the human belang novel describes lineage, bontang forest rituals, and livelihoods. The results of this analysis reveal the meaning of lies in the form of signs in the novel such as to balo's belief in the existence of bontang forests, the community's stigma of the curse of to balo on the condition of the skin, the truth about the existence of to balo, and the belief in the existence of chosen people. Data showing the existence of symbols contained in the novel Human Belang in connection with Umberto Eco's general semiotic theory based on the theory of lie by linking denotation and connotation meanings that have been agreed upon by cultural units to obtain true interpretations and seen from political boundaries. Keywords: Umberto Eco, Cultural Representation, To Balo Tribe